51. Text-based Conferencing: Features vs. functionality - Anderson, Lynn; McCarthy, Kathy (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
This report examines three text-based conferencing products: WowBB, Invision Power Board, and vBulletin. Their selection was prompted by a feature-by-feature comparison of the same products on the WowBB website. The comparison chart painted a misleading impression of WowBB's features in relation to the other two products; so the evaluation team undertook a more comprehensive and impartial comparison using the categories and criteria for online software evaluation developed by the American Society for Training and Development (ASTD). The findings are summarised in terms of the softwares' pricing, common features/ functions, and differentiating features.